2018
DOI: 10.1080/10705511.2018.1541745
|View full text |Cite
|
Sign up to set email alerts
|

The Detection and Modeling of Direct Effects in Latent Class Analysis

Abstract: Several approaches have been proposed for latent class modeling with external variables, including one-step, two-step, and three-step estimators. However, very little is known yet about the performance of these approaches when direct effects of the external variable to the indicators of latent class membership are present. In the current article, we compare those approaches and investigate the consequences of not modeling these direct effects when present, as well as the power of residual and fit statistics to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…In addition, a model-building strategy was presented which can be used to find the external variables causing DIF, thus making the new methodology practically applicable. The approach was illustrated with a real-life application using a data set from Hagenaars (1993), which showed that using the new approach may have a large impact on the step-three parameter estimates.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, a model-building strategy was presented which can be used to find the external variables causing DIF, thus making the new methodology practically applicable. The approach was illustrated with a real-life application using a data set from Hagenaars (1993), which showed that using the new approach may have a large impact on the step-three parameter estimates.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, it should be noted that in practice the amount of bias will depend on factors such as strength and direction of the DIF, number of DIF items, and DIF being uniform or non-uniform. (Janssen et al, 2019;Masyn, 2017). We noticed that even the settings used in the step-three model estimation matter: the amount of bias changed with proportional instead of a modal class assignment or with BCH instead of maximum likelihood adjustment.…”
Section: A Demonstration Using a Constructed Data Examplementioning
confidence: 98%
See 2 more Smart Citations
“…Beyond these criteria, interpretability of the results was also considered [ 44 ]. The recent developments in LCA consider relating the indicators to the latent classes and also relating the classes extracted to a set of external variables [ 45 ]. Once the number of latent classes was determined, groups of participants based on these classes were compared based on several markers of successful aging.…”
Section: Methodsmentioning
confidence: 99%